41‐3: Invited Paper: High Resolution Stretchable Micro‐LED Displays. Issue 1 (28th June 2022) - Wang, Cheng-Liang; Ho, Shu-Te; Wang, Wen-Ting; Chen, Chia-Kai; Yang, Ching-Fei; Jiang, Cheng-Wei; Wu, Chih-Hung; Su, Wei-Jen; Chi, Hong-Sian; Lin, Shin-Ru; Hung, Wei-Lun; Tsai, Yi-Wei; et al.
Abstract : The RGB micro‐LED display has been demonstrated to withstand mechanical strain during out‐of‐plane periodically deformation. In this work, the high pixel density (>139‐PPI) and high strain tolerance of circuits were achieved by utilizing the novel design of the island‐bridge structure under the compact pixel arrangement. Light absorbent was adopted into a stretchable display to reduce ambient back light and ambient reflection for the dark mode of a panel